2017
DOI: 10.1259/bjr.20160361
|View full text |Cite
|
Sign up to set email alerts
|

Chronological changes of radiofrequency ablation zone in rabbit liver: an in vivo correlation between gross pathology and histopathology

Abstract: Objective: To examine the gross pathology and histopathology of ablation zones created from radiofrequency (RF) ablation and to correlate their chronological changes. Methods: A total of 48 in vivo ablation zones (16 rabbit livers) were obtained immediately after and also 30 min, 1 h and 2 h after RF ablation and were subjected to haematoxylin and eosin (H&E) staining, nicotinamide adenine dinucleotide (NADH) diaphorase staining, terminal deoxynucleotidyl transferase dUTP nick end labelling (TUNEL) staining. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Third, a histologic analysis was not performed to evaluate cell necrosis. However, previous studies have demonstrated that central white zone corresponds with total necrosis, whereas peripheral red zone is a mixture of dying and dead cells [13]. Considering that the peripheral red zone was thin in our study, this would not significantly affect our results.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…Third, a histologic analysis was not performed to evaluate cell necrosis. However, previous studies have demonstrated that central white zone corresponds with total necrosis, whereas peripheral red zone is a mixture of dying and dead cells [13]. Considering that the peripheral red zone was thin in our study, this would not significantly affect our results.…”
Section: Discussionmentioning
confidence: 48%
“…The ablation volume was also significantly larger with ICWT than that with ICT (p ¼ .003) due to the differences in ablation zone diameters. The thickness of the peripheral red zones, comprising a mixture of damaged and dead cells rather than totally dead cells [13], was small in both electrodes, indicating that the rather short 6-min ablation time was sufficient in creating a 3-cm ablation zone. The amount of applied energy was also bigger with ICWT than that with ICT (p ¼ .003), which would correspond with the larger ablation volume since the amount of applied energy is reported to correspond to the volume of the abla-tion zone [21] and thus would be more time-energy efficient [22].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Moreover, we estimated ablation volumes by analysing macroscopic photographs taken only from a single slice. While evidence exists in support of the use of gross pathological examination as a reliable indicator of lethally damaged tissue in RFA (Gemeinhardt et al, 2016;Song et al, 2017), a real 3D ablation analysis (either performed by multi slice histology, macroscopy or CT) might have improved the accuracy of our results and should be preferred for the assessment of in vivo ablated zones.…”
Section: Discussionmentioning
confidence: 98%
“…The white zone proportion of AMm at a 25-mm interelectrode distance was the lowest in the DSM mode, although the ablative margin with DSM was the largest when compared with that in the other energy modes. A previous study demonstrated that the central white zone corresponded to total necrosis, whereas the peripheral red zone was a mixture of dying and dead cells [ 14 ]. Although it is unknown which of the two zones (white zone only or white + red zone) should be considered in the evaluation of the true ablation zone, a larger white zone would be preferable to ensure complete tumor necrosis.…”
Section: Discussionmentioning
confidence: 99%